Penerapan Metode SAW untuk Penentuan Pemenang Lomba Desain Grafis - Arysespajayadi; Nisa Miftachurohmah; Melda Agnes Manuhutu (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2024)
The evaluation of graphic design competitions often faces challenges related to jury subjectivity, which can affect the final results and lead to dissatisfaction among participants. This study aims to apply the Simple Additive Weighting (SAW) method in the scoring system of graphic design competitions to achieve more objective and transparent assessments. The SAW method is used to evaluate participants based on four main criteria: aesthetics, originality, theme relevance, and technical quality. Each criterion is assigned a weight according to its level of importance, and preference values are calculated to determine the winner. The results of the study show that the application of the SAW method successfully reduces subjective bias and increases consistency in scoring. Participants with the highest preference values are selected as the winners, with the system facilitating a more objective evaluation process. This research also contributes to the development of more transparent assessment systems in various creative competitions. However, determining the weighting of criteria remains a challenge that requires further discussion between judges and organizers.